The Influence of Marketing Information Systems and Product Quality on Customer Purchasing Decisions at PT. Schneider Electric in Bandung City, West Java - Ai Sri Rahayu (International Journal of Economics, Commerce, and Management, 2024)
Information technology is developing rapidly, making it easier for companies to interact between countries and consumers. So that the company improves its competence to increase market share. The marketing information system helps companies to find out the needs of consumers and consumers can easily find information about a product from the company. The purpose of this study is to determine the influence of marketing information systems and product quality on purchasing decisions. The analysis unit of PT. Schneider Electric in the city of Bandung, West Java. The source of research data is primary, namely distributing questionnaires online and secondary data. The population is potential customers in the city of Bandung, the sample drawing technique uses a census of 100 customers. The results of the descriptive analysis of the marketing information system, product quality and purchase decisions in the score interval of 421-501 are very good. Associative analysis F calculates > F table so that there is an influence of marketing information systems and product quality on purchasing decisions At PT. Schneider Electric in the city of Bandung, West Java by 99.2%.